13C Solid State Nuclear Magnetic Resonance and µ-Raman Spectroscopic Characterization of Sicilian Amber. Issue 8 (August 2016) - Barone, Germana; Capitani, Donatella; Mazzoleni, Paolo; Proietti, Noemi; Raneri, Simona; Longobardo, Ugo; Di Tullio, Valeria
13 C cross-polarization magic angle spinning (CPMAS) nuclear magnetic resonance (NMR) and µ-Raman spectroscopy were applied to characterize Sicilian amber samples. The main goal of this work was to supply a complete study of simetite, highlighting discriminating criteria useful to distinguish Sicilian amber from fossil resins from other regions and laying the foundations for building a spectroscopic database of Sicilian amber. With this aim, a private collection of unrefined simetite samples and fossil resins from the Baltic region and Dominican Republic was analyzed. Overall, the obtained spectra permitted simetite to be distinguished from the other resins. In addition, principal component analysis (PCA) was applied to the spectroscopic data, allowing the clustering of simetite samples with respect to the Baltic and Dominican samples and to group the simetite samples in two sets, depending on their maturity. Finally, the analysis of loadings allowed for a better understanding of the spectral features that mainly influenced the discriminating characteristics of the investigated ambers.